Stochastic Block Model Reveals Maps of In Applied Mathematics Studies Using VOS Viewer - Karim, Arifin; Soebagyo, Joko; Edy Purwanto, Sigid (International Journal of Progressive Mathematics Education, 2021)
Bibliometric analysis is the mapping of research research trends by processing metadata from Google Scolar. The aim is to find out research trends in applied mathematics. The research was conducted on April 30, 2021 through searching the Google Scholar database with the keywords applied mathematics with the publication name journal and the maximum number of results is 500 journals as a sample. Metadata retrieval using the Publish or Perish (POP) application version 7.31. The PoP data were then analyzed descriptively based on the publication year, publisher name, researcher productivity, and journal ranking. To get an accurate map of research developments, PoP data is exported to Exel CSV and Result as RIS file formats. The CSV data was created in a pivot table and the RIS data was analyzed using the VOSViewer (VV) application. The results of the research show that the number of publications of research results in the years 2005-2021 has fluctuated and is mostly published in Elsevier. The most prolific foreign researcher in publishing research results is Biher Bist with 14 articles. The VV visualization shows that the map of the development of applied mathematics research is divided into 5 clusters. Cluster 1 consists of 27 topics, cluster 2 consists of 15 topics, cluster 3 consists of 10 topics, cluster 4 consists of 7 topics, and cluster 5 consists of 3 topics with the most research covering mathematics, paper, problem, solution, system, university, department, science.